2002
DOI: 10.4049/jimmunol.169.11.6261
|View full text |Cite
|
Sign up to set email alerts
|

CD4 Dimers Constitute the Functional Component Required for T Cell Activation

Abstract: The CD4 molecule plays a key role in the development and activation of helper T cells. Dimerization and oligomerization is often a necessary step in the function of several cell surface receptors. Herein, we provide direct biochemical evidence confirming the presence of CD4 as dimers in transfected cells from hemopoetic and fibroblastic origin as well as in primary T cells. Such dimers are also observed with murine CD4 confirming selective pressure during evolution to maintain such a structure. Using a series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 57 publications
5
47
1
Order By: Relevance
“…Confirming the crystallographic data, we identified K318 and Q344, two highly conserved residues within the D4 domain, as critical for CD4 dimer formation, assessed biochemically. Although we have shown that CD4 dimers constitute the functional component of CD4 for cytokine production, the mechanism involved is unclear (23).…”
Section: T He Adaptive Immune Response Is Activated When Tcrs On the mentioning
confidence: 89%
See 2 more Smart Citations
“…Confirming the crystallographic data, we identified K318 and Q344, two highly conserved residues within the D4 domain, as critical for CD4 dimer formation, assessed biochemically. Although we have shown that CD4 dimers constitute the functional component of CD4 for cytokine production, the mechanism involved is unclear (23).…”
Section: T He Adaptive Immune Response Is Activated When Tcrs On the mentioning
confidence: 89%
“…Although this mutation abrogates CD4 dimerization, it does not affect the conformational integrity of the CD4 molecule (23). The chimeric proteins were stably expressed in the CD4 Ϫ CD8 Ϫ murine T cell hybridoma 3DT52.5.8 (17,23,31,32).…”
Section: Functional Cd4 Dimerization On the Cell Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…In murine CD4, indications are found for the formation of a disulfide linked dimer formed by domain swapping of D2 giving disulfide-bonds between C 130 in one monomer and C 159 in the other one [37]. In human CD4, K 318 and Q 344 were identified as important residues for a non-covalent dimer association between D4 of adjacent CD4 molecules [38], and it has been speculated that this aligning of two CD4 monomers gives the opportunity for efficient forming of a covalently disulfide linked CD4 dimers [37]. has been demonstrated that CD4 dimerization is required for CD4-mediated T-cell activation [38,39], and it has been indicated that the preferred MHC class II co-receptor is disulfide linked dimeric CD4 [37].…”
Section: Discussionmentioning
confidence: 99%
“…In human CD4, K 318 and Q 344 were identified as important residues for a non-covalent dimer association between D4 of adjacent CD4 molecules [38], and it has been speculated that this aligning of two CD4 monomers gives the opportunity for efficient forming of a covalently disulfide linked CD4 dimers [37]. has been demonstrated that CD4 dimerization is required for CD4-mediated T-cell activation [38,39], and it has been indicated that the preferred MHC class II co-receptor is disulfide linked dimeric CD4 [37]. Also, the connecting peptide region of the two-domain CD4-like molecules can be important for MHC binding, as a high percentage of prolines (about 21% in halibut CD4-2) may allow an extended structure so that the D1 of CD4-2 can reach the MHC molecule.…”
Section: Discussionmentioning
confidence: 99%